Paul and Scripture - Moyise, Steve (Grand Rapids, Mich. : Baker Academic, 2010)
Steve Moyise, an expert on the use of the Old Testament in the New, discusses Paul's handling of creation stories, Abraham, Moses, the Law, the Prophets, and the Writings. He then assesses competing contemporary approaches to Paul's interpretations of Scripture. --from publisher description
Paul and the creation stories -- Paul and Abraham -- Paul and Moses -- Paul and the law -- Paul and the prophets : Israel and the Gentiles -- Paul and the prophets : the life of the Christian community -- Paul and the writings -- Modern approaches to Paul's use of scripture.
'Studying the New Testament use of the Old Testament'--Cover.
Includes bibliographical references (p. 135-149) and indexes.
Keywords: Bible. -- Theology; Bible. -- Relation to the Old Testament; Bible. -- Relation to the Epistles of Paul; Paul and Old Testament; Paul and The Law; Paul and His Teachings of Scripture